Diagnóstico situacional dos pacientes potenciais aos cuidados paliativos no Hospital das Clínicas de Vitória-ES - Gouvea, Maria da Penha Gomes (2015)
Major changes have occurred in Brazil`s mortality scenery. The epidemiological and demographic transition presents a challenge to the management of public health since No communicable Diseases Chronic (NCDs) have now the highest incidence in the population demanding changes in health services. In this scenario arises Palliative Care (PC), a therapeutic approach for patients with life-threatening diseases that seeks to mitigate the pain and alleviate the suffering of patients and their families. The objective of this research was to identify potential patients to palliative care by creating a situational diagnosis of admitted patients at the University Hospital Cassiano Antônio Moraes - HUCAM (Hospital das Clinicas). To this end, documentary and quantitative research was conducted using data from medical records followed by application of the Palliative Performance Scale (PPS). Among the identified patients, most of them had cancer and were aged over 60 years. Also, the majority of the group were male and patients with prior hospitalizations in the institution. According to the PPS, most patients had scores that classified them in immediate need of PC. The result of this research points to the urgency of palliative care´s implementation at HUCAM as it revealed a significant group of patients facing life-threatening diseases, some already in imminent death process. This survey also supplied a gap that existed in knowledge about the profile of a specific population among patients of HUCAM leading to the excellence in health service as well as seeking to optimize the use of hospital beds of medium and high complexity